High-performance sensorless nonlinear power control of a flywheel energy storage system - Amodeo, Santiago Jose (2009)
The flywheel energy storage systems (FESS) can be used to store and release energy in high power pulsed systems. Based on the use of a homopolar synchronous machine in a FESS, a high performance modelbased power flow control law is developed using the feedback linearization methodology. This law is based on the voltage space vector reference frame machine model. To reduce the magnetic losses, a pulse amplitude modulation driver for the armature is more adequate. The restrictions in amplitude and phase imposed by the driver are also included. A full order Luenberger observer for the torque angle and rotor speed is developed to implement a sensorless control strategy. Simulation results are presented to illustrate the performance.